Analysis of the sustainability of productive carbon forests in Garut, West Java, Indonesia - SURYA AKBAR PUTRA; DODIK RIDHO NURROCHMAT; HANDIAN PURWAWANGSA; NUGRAHA AKBAR NURROCHMAT; MUDRIKA QANITHA; FAIZAL MUTAQIN (Society for Indonesian Biodiversity, 2025)
Abstract. Putra SA, Nurrochmat DR, Purwawangsa H, Nurrochmat NA, Qanitha M, Mutaqin F. 2025. Analysis of the sustainability of productive carbon forests in Garut, West Java, Indonesia. Biodiversitas 26: 3218-3226. This study discusses the sustainability of the Productive Carbon Forest (PCF) program in Garut District, West Java, Indonesia. The purpose of this study is to analyze the sustainability index of the PCF program. The data used in this study are primary data (expert interviews, field surveys) and secondary data (library, agency reports). This study uses Multidimensional Scaling (MDS) techniques to analyze the dimensions of sustainability, with a scale of 0 (lowest) to 2 (highest), along with Rapid Appraisal for Private Forests (RAP-PFOREST) support, to assess the level of similarity and dissimilarity for each dimension. The results showed that Halimun community forestry is in the very sustainable category with a sustainability score of 80.35%, and produces 12 sensitive attributes, while Giriawas social forestry is in the moderately sustainable category with a sustainability score of 63.94% and produces 12 sensitive attributes that affect the management of the PCF program. Based on the results of the study at the two locations of the PCF program implementation, this study concluded that there were differences in the sustainability index values ??at the two locations of the program implementation, meaning that at the Giri Purnama Alam social forestry location, there is a need to improve technical assistance for adaptive management and monitoring. We recommend involving various stakeholders to encourage them to become a strategic reference in formulating sustainable forestry policies in the future.